Monogenea (van Beneden, 1858) Carus, 1863 de peces marinos del litoral mexicano del Golfo de México y del Mar Caribe. VI - Caballero C., Eduardo; Bravo-Hollis, Margarita (Revista de Biología Tropical, 1973)
A new genus and species of Monogenea, Ahpua piscicola, is described from the gills of the marine fish Polydaclylus octonemus (Girard, 1858), family Polynemidae Günther, 1860, from the western edge of the Gulf of Mexico. The new genus and species are referred to the family Discocotylidae Price, 1936, on the basis of the from and structure of the opisthohaptor and of the clamps, as well as those of the reproductive organs. Because oE its eight sessile clamps, four large and four small, on the irregular opisthohaptor, it cannot be placed in any of the 20 genera currently constituting this family, therefore justifying establishment of the new genus. The proposed genus name is that of the Mayan god Ahpua, protector of fishermen.